Innovation in cultural heritage management as a sustainable tourism attraction: A qualitative study of Kota Tua Padang tourism village - Callista Teja; Feronika Berutu (Satwika : Kajian Ilmu Budaya dan Perubahan Sosial, 2025)
This study is titled "Innovation in Cultural Heritage Management as a Sustainable Tourism Attraction in the Kota Tua Padang Heritage Village." The study aims to analyze the innovations applied in the management of cultural heritage in Kota Tua Padang Heritage Village, as well as the challenges and obstacles faced in creating sustainable tourism. This research uses a qualitative descriptive approach with data collection methods including interviews, observations, and documentation. Data were obtained from various sources, including tourism offices, heritage village managers, business owners, and tourists visiting the heritage village. The findings show that the innovations applied in the cultural heritage management in the heritage village include the revitalization of historical buildings, the development of culture-based tourism facilities, and the use of digital technology for promotion and information. However, the study also identifies several management challenges, including limited infrastructure, a lack of a structured management system, and low awareness among visitors of the preservation of culture and the environment. The application of sustainable tourism principles has been carried out by considering economic, social, and environmental aspects, but there is still room for improvement in management and increasing local community involvement. The study's results affirm that innovations in physical revitalization and digitalization can strengthen sustainable cultural tourism management and cultural heritage preservation. This study is expected to contribute to the development of sustainable tourism based on cultural heritage preservation in the area.   Penelitian ini berjudul "Inovasi Pengelolaan Cagar Budaya sebagai Daya Tarik Pariwisata Berkelanjutan di Desa Wisata Kota Tua Padang." Penelitian ini bertujuan untuk menganalisis inovasi dalam pengelolaan cagar budaya yang diterapkan di Desa Wisata Kota Tua Padang, serta tantangan dan hambatan yang dihadapi dalam menciptakan pariwisata berkelanjutan. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan metode pengumpulan data melalui wawancara, observasi, dan dokumentasi. Data diperoleh dari berbagai sumber, termasuk dinas pariwisata, pengelola desa wisata, pelaku usaha, dan wisatawan yang mengunjungi desa wisata. Hasil penelitian menunjukkan bahwa inovasi yang diterapkan dalam pengelolaan cagar budaya di Desa Wisata mencakup revitalisasi bangunan bersejarah, pengembangan fasilitas wisata berbasis budaya, serta pemanfaatan teknologi digital untuk promosi dan informasi. Namun, penelitian ini juga mengidentifikasi beberapa tantangan dalam pengelolaan, seperti keterbatasan infrastruktur, kurangnya sistem pengelolaan yang terstruktur, serta kesadaran pengunjung yang masih rendah terhadap pelestarian budaya dan lingkungan. Penerapan prinsip pariwisata berkelanjutan telah dilakukan dengan mempertimbangkan aspek ekonomi, sosial, dan lingkungan, namun masih terdapat ruang untuk perbaikan dalam pengelolaan dan peningkatan keterlibatan masyarakat lokal. Hasil penelitian menegaskan bahwa inovasi dalam revitalisasi fisik dan digitalisasi mampu memperkuat pengelolaan pariwisata budaya yang berkelanjutan dan pelestarian cagar budaya. Penelitian ini diharapkan dapat memberikan kontribusi dalam pengembangan pariwisata berkelanjutan yang berbasis pelestarian cagar budaya di kawasan ini.